Impact of digital marketing and price towards intention to buy mediating by brand awareness in interior design business - Liem, Cerrien (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
As technology advances in our generation, digital marketing has become an effective method for promoting a firm. In terms of interior design, each organization has a unique style and set of features, beginning with the design of ideas, design preferences, and design objectives to be attained. Therefore, digital marketing assists in demonstrating to the public what sort of interior services a firm engaged in creative intends to offer. With the aid of social media marketing and pricing, instill value and brand awareness in the minds of clients seeking interior design services, resulting in their intention to purchase the services. This study seeks to investigate and assess the impact of digital marketing methods and prices on business interior design and the formulation of client purchase intentions. This study employs quantitative methods. In this study, quantitative data will be measured using the Likert Interval scale. The study's findings indicate that content marketing (X1) has a favorable and statistically significant impact on brand awareness. Brand awareness is positively and significantly affected by website quality (X2). Brand awareness is positively and significantly affected by online advertising (X3). Price (X4) has a large and favorable impact on brand recognition.